The Influence Of Influencer Marketing, Digital Advertising, Online Customer Reviews And Perceived Value On Purchasing Decisions In The Ms Glow E-Commerce Brand (Study Of Ms Glow Users In Sidoarjo) - Choirunnisa, Nurussyahidah; Muhammad Yani; Lilik Indayani (Al Tijarah, 2024)
E-commerce has gotten to be one of the foremost prevalent computerized acquiring and offering media and has gotten to be a prevalent online shopping stage by businesses. Online shopping offers comfort counting boundless get to to time and area, simple get to to item data, cost and quality comparison, and more. The reason of this think about is to analyze the affect of esteem on influencer promoting, advanced promoting, online client surveys, and acquiring choices of MS Gleam Sidoarjo e-commerce brands. For obscure populaces, utilize the favor condition to calculate the number of tests with 100 respondents. This ponder employments a quantitative approach and SmartPLS examination apparatuses. The comes about showed that influencer showcasing incorporates a critical positive affect on obtaining choices, online client reviews have a critical positive affect on acquiring choices, and seen esteem features a noteworthy positive affect on MS Gleam e-commerce brands.